2010
DOI: 10.1057/grir.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Jumps and Stochastic Interest Rates on the Fair Costs of Guaranteed Minimum Death Benefit Contracts

Abstract: The authors offer a new perspective to the domain of guaranteed minimum death benefit contracts. These products have the particular feature to offer investors a guaranteed capital upon death. A complete methodology based on the generalized Fourier transform is proposed to investigate the impacts of jumps and stochastic interest rates. This paper thus extends Milevsky and Posner (2001). In contrast to their results, the fair costs of the guarantee feature are found to be substantially higher in this more genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For this last point, mortality tables or laws can be used. This determination of fair fees is a generalization of Milevsky and Posner, () and Quittard‐Pinon and Randrianarivony, ().…”
Section: Productsmentioning
confidence: 96%
“…For this last point, mortality tables or laws can be used. This determination of fair fees is a generalization of Milevsky and Posner, () and Quittard‐Pinon and Randrianarivony, ().…”
Section: Productsmentioning
confidence: 96%
“…22 In their paper, Derman and Taleb (2005) have shown that dynamic hedging is neither strictly required nor strictly necessary for plausibly valuing options. 23 Quittard-Pinon and Randrianarivony (2011). 24 See Lai et al (2008).…”
Section: Demutualisation and Performance Of Property-liability Insuramentioning
confidence: 99%